Geographic Information System Mapping the Location of Economically Weak Population at the Central Bureau of Statistics of Southwest Sumba Regency - Marselina Bulu; Cecilia Dai Payon Binti Gabriel; Titus Kurra (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Geographic information systems are data placed in the context of space and time using computer systems used in the process of storing, manipulating, and analyzing geographic information. The purpose of this research is that the GIS application can help provide information on mapping the location of the economically weak population to the entire community quickly and easily. In addition, it can facilitate employees of the BPS Office of Southwest Sumba Regency in providing correct and accurate data information. The results of this study can help us find the location point quickly.